Urgensi Pembelajaran PAI Dalam Menumbuhkan Kedisiplinan Siswa Di Sekolah SMA Plus At-Tadzkir Dalam Naungan Pondok Pesantren At-Tadzkir Majalengka - Yeyen Lenggawati (4, 2025)
This study aims to analyze the urgency of Islamic Religious Education (PAI) learning in fostering student discipline at At-Tadzkir Plus High School under the auspices of the At-Tadzkir Majalengka Islamic Boarding School. PAI learning in the context of Islamic boarding schools has a strategic role not only as a delivery of religious material, but also as an instrument for forming disciplined character through internalizing the values ​​of faith, piety, and noble morals. This study uses a qualitative approach with descriptive methods, collecting data through observation, interviews, and documentation of PAI teachers, Islamic boarding school administrators, and students. The results show that PAI learning contributes significantly to the formation of student discipline through various programs, such as habituation of worship, Islamic boarding school regulations, teacher role models, and daily religious activities integrated with school activities. The religious and structured Islamic boarding school environment supports students in developing orderly lifestyles, responsibility, and self-control. In addition, PAI plays a role as a moral fortress that protects students from the negative influences of modern developments and helps them develop personalities with strong character. In conclusion, Islamic Religious Education (PAI) learning is crucial for fostering student discipline at At-Tadzkir Plus High School. PAI not only fulfills curricular needs but also serves as a primary foundation for developing noble character, as part of the national education goals. Religious values-based education in Islamic boarding schools has proven effective in creating a disciplined, moral, and responsible generation, thus making a positive contribution to the nation's future. Abstrak Penelitian ini bertujuan untuk menganalisis urgensi pembelajaran Pendidikan Agama Islam (PAI) dalam menumbuhkan kedisiplinan siswa di SMA Plus At-Tadzkir yang berada di bawah naungan Pondok Pesantren At-Tadzkir Majalengka. Pembelajaran PAI dalam konteks sekolah berbasis pesantren memiliki peran strategis tidak hanya sebagai penyampaian materi keagamaan, tetapi juga sebagai instrumen pembentukan karakter disiplin melalui internalisasi nilai iman, takwa, dan akhlak mulia. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, mengumpulkan data melalui observasi, wawancara, dan dokumentasi terhadap guru PAI, pengelola pesantren, dan siswa. Hasil penelitian menunjukkan bahwa pembelajaran PAI berkontribusi signifikan terhadap pembentukan kedisiplinan siswa melalui berbagai program, seperti pembiasaan ibadah, tata tertib pesantren, keteladanan guru, serta kegiatan keagamaan harian yang terintegrasi dengan aktivitas sekolah. Lingkungan pesantren yang religius dan terstruktur mendukung siswa dalam membangun pola hidup tertib, tanggung jawab, dan kemampuan mengendalikan diri. Selain itu, PAI berperan sebagai benteng moral yang melindungi siswa dari pengaruh negatif perkembangan zaman dan membantu mereka membentuk kepribadian yang berkarakter kuat. Kesimpulannya, pembelajaran PAI memiliki urgensi yang sangat besar dalam menumbuhkan kedisiplinan siswa di SMA Plus At-Tadzkir. PAI bukan hanya memenuhi kebutuhan kurikuler, tetapi juga menjadi fondasi utama dalam pembentukan karakter mulia sebagai bagian dari tujuan pendidikan nasional. Pendidikan berbasis nilai religius di sekolah pesantren terbukti efektif dalam menciptakan generasi yang disiplin, berakhlak, dan bertanggung jawab, sehingga memberikan kontribusi positif bagi masa depan bangsa